Normal reference ranges for left ventricular dimensions in preterm infants - Lulu Abushaban; Mariappa Thinakar Vel; Jebaraj Rathinasamy; Prem N Sharma (Wolters Kluwer Medknow Publications, 2014)
Objective To establish normal reference ranges for the left ventricular dimensions in preterm infants and their correlation with gestational age, body weight and chronological age. Materials and Methods In a prospective study, 268 preterm babies, who fulfilled the criteria for inclusion, were examined in Kuwait during the years (2008-2010). Echocardiograms were performed to measure the left ventricular dimensions on 0-6 day(s) of life and at weekly intervals until they reached 36 weeks. The gestational age was grouped into three: 24-27, 28-31 and 32-35 weeks, and body weight into five: ≤999, 1,000-1,499, 1,500-1,999, 2,000-2,499 and ≥2,500 grams. The overall group differences were compared for each period of life: 0-6 days, 1-2, 3-4 and ≥5 weeks. Results The mean gestational age was 29.8 (± 2.38 SD) weeks, ranging between 24 and 35, and the mean body weight 1,479 (± 413 SD) grams, ranging between 588 and 3380. At the first scan (0-6 days of life), all the left ventricular measurements correlated well (P < 0.001) with body weight, and the same was observed with gestational age, except for left ventricular posterior wall thickness at end-systole and end-diastole. A significant gradual increase was noticed in all the dimensions with body weight during each period of life. However, with respect to gestational age, an increase was observed in all the dimensions during first four weeks, but the rate of increase became less after 5 weeks of life. Overall, a progressive and significant increase in all left ventricle measurements was observed during the first nine weeks of life. Conclusion The left ventricular dimension measurements were found to have significant correlation with both gestational age and body weight. The study also provides reference data, which can be used as normal reference tool for left ventricular dimensions for preterm infants against the gestational age, body weight and chronological age.